Analisis Indeks Kepuasan Layanan Akademik Mahasiswa Untuk Meningkatkan Layanan Manajemen Pada Program Pascasarjana Prodi PAH STAHN Mpu Kuturan Singaraja - I Nyoman Raka; I Nyoman Miarta Putra (Cetta: Jurnal Ilmu Pendidikan, 2022)
This study raised the issue of the academic service satisfaction index of STAHN Mpu Kuturan Singaraja postgraduate students. This issue is important to research in order to improve academic service management in the STAHN Mpu Kuturan Singaraja postgraduate program. In addition, the high fluctuation of public interest to study in postgraduate studies is also a consideration for this study. Thirty-five students in the first batch, increased to 52 students in the second batch; then dropped to 39 students in the third batch, and dropped again to 23 students in the fourth batch. The fluctuation of public interest in entering postgraduate is also the reason for the importance of this research. This study used a quantitative descriptive design. The five service dimensions that become indicators of student satisfaction are: the reliability dimension, the Responsiveness dimension, the Assurance dimension, the Empathy dimension and the Tangibles dimension. The results of data analysis showed that in general the academic services received by STAHN Mpu Kuturan Singaraja postgraduate students were satisfactory. In detail, the percentage of student satisfaction with academic services at postgraduate is as follows: 3% of postgraduate students are not satisfied with the academic services they receive; 12% of postgraduate students are dissatisfied with the academic services they receive; 41% of students are quite satisfied with the academic services they receive; 35% of students are satisfied with the academic services they receive, and 8% of students are very satisfied with the academic services they receive.